Regulasi Hukum Lingkungan dalam Pencemaran Limbah Industri di Sungai Citarum: Kepatuhan Industri dan Dampaknya pada Lingkungan - Devandra Berliana Budisafitri; Ericko Arwinda Al Iyad; Nazwa Hawwa Audica (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
The Citarum River, as one of the important environmental assets in Indonesia, has experienced serious pollution due to industrial waste. Environmental legal regulations have been implemented to address these issues, but questions arise regarding the effectiveness of their implementation. This article analyzes the effectiveness of environmental legal regulations in handling cases of factory waste pollution in the Citarum River, with a focus on the level of industrial compliance and its impact on the environment. This study uses a qualitative approach by reviewing the applicable environmental legal regulations, as well as analyzing the level of industry compliance with these regulations. In addition, the impact of compliance or violations on the environment is also evaluated. The results of the analysis show that although environmental legal regulations exist, their implementation is still not optimal. Many factories still violate the limits that have been set, either because of a lack of strict law enforcement or because of a lack of awareness of the importance of environmental conservation. As a result, the Citarum River continues to experience pollution which is detrimental to the environment and public health. Existing environmental legal regulations are not effective enough in handling cases of factory waste pollution in the Citarum River. More serious efforts are needed from the government, industry and society to overcome this problem. Concrete steps are needed to increase industrial compliance, reduce waste pollution, and preserve the Citarum River environment for the welfare of the community and sustainability of the ecosystem. Further research can be conducted to evaluate the implementation of remedial actions and their impact on future environmental conditions. This article concludes the need for improvement measures in the implementation of environmental legal regulations, including stricter law enforcement and efforts to increase environmental awareness among industry. Apart from that, cooperation between government, industry and civil society is also important to achieve the restoration of a clean and healthy Citarum River.